1987
DOI: 10.2527/jas1987.6561727x
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Calcium, Phosphorus, Magnesium and Vitamin D that Influence their Status in Domestic Meat Animals

Abstract: Known and possible interactions between Ca, P, Mg, parathyroid hormone (PTH), calcitonin (CT), vitamin D and its metabolites, and interactions of each of these with other factors plus complexities and possible variations between and within domestic animal species, such as age, sex, physiologic state (i.e., pregnancy, lactation and growth) and diet, make Ca, P and Mg metabolism extremely dynamic and complex. Many advances have been made in understanding these interactions and how each of these factors is contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
9

Year Published

1993
1993
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 65 publications
(80 reference statements)
1
31
0
9
Order By: Relevance
“…A homeostase do cálcio é regulada pela a calcitonina, pelo paratormônio (PTH) e pela 1,25-dihidroxivitamina D (Littledike & Goff 1987, DeGaris & Lean 2008. Quando as concentrações de cálcio são menores que o intervalo de referência, como observada nos animais próximo ao parto, ocorre à liberação do paratormônio, que aumenta a reabsorção óssea e ativa a 1,25-dihidroxivitamina D. A vitamina D atua aumentando a reabsorção tubular renal e a absorção intestinal de cálcio (DeGaris & Lean 2008, Taylor et al 2008, Goff 2009).…”
Section: Quadro 4 Valores De Condição Corporal Das Vacas Mestiças Plunclassified
See 2 more Smart Citations
“…A homeostase do cálcio é regulada pela a calcitonina, pelo paratormônio (PTH) e pela 1,25-dihidroxivitamina D (Littledike & Goff 1987, DeGaris & Lean 2008. Quando as concentrações de cálcio são menores que o intervalo de referência, como observada nos animais próximo ao parto, ocorre à liberação do paratormônio, que aumenta a reabsorção óssea e ativa a 1,25-dihidroxivitamina D. A vitamina D atua aumentando a reabsorção tubular renal e a absorção intestinal de cálcio (DeGaris & Lean 2008, Taylor et al 2008, Goff 2009).…”
Section: Quadro 4 Valores De Condição Corporal Das Vacas Mestiças Plunclassified
“…A concentração sérica normal de cálcio no bovino adulto se mantém em torno de 8,5 a 10 mg/dL sendo que 45 a 50% estão na forma livre (Littledike & Goff 1987, Larsen 2001, Goff 2004. A variação da concentração de cálcio, principalmente na forma ionizada, não deve fugir deste valor, do contrário ocorrem várias consequências graves para os processos fisiológicos e para a vida, como a perda do potencial elétrico e condutividade de membrana de músculos e nervos (Littledike & Goff 1987, NRC 2001.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…II. The "Low calcium principle" (low calcium intake via the feed) is aimed at affecting the calcium absorption in the intestines and the mobilisation mechanism by under-supplying the organism for a period [73,117]. The philosophy behind the "low calcium principle" is based on the fact that there is a homeostatic regulation of calcium absorption.…”
Section: Strategies Of Adapting For Mobilisation and Calcium Absorptionmentioning
confidence: 99%
“…It may be due to larger body size than local. However, a study conducted by [14] reported the greater hypocalcaemia cases in local indigenous goat. In present study, the unable to move was predominant clinical sign in hypocalcemic cattle which is well supported by earlier studies [15][16][17].…”
Section: Discussionmentioning
confidence: 99%